Ambulatory Nurse Education Improves Metabolic Profile and Physical Activity in Patients with Cardiovascular Disease (International Journal of Nursing Education, 2020)
Introduction: Although interventions combining patient education and post discharge management havedemonstrated benefits in patients with cardiovascular disease the benefit attributable to ambulatory nurseeducation (ANE) alone is uncertain.Material and Method: A quasi experimental study was conducted in Specialist Cardiology Ambulance D& D in Pristinaamong 98 patients. Ambulatory nurse education was implemented to assess the effectivenesson awareness on life style where pretest and posttest design without control group was used. A completeclinical and laboratory measurements before and after ANE (at 30, 60 and 90 days) were performed. Theclinical outcome were physical activity, body mass index, blood pressure, lipid and diabetic profile. Thepre-post tested (validity, reliability and pilot testing) structured questionnaire was used for data collection.Results: At follow up to 90 days, in patients that underwent ANE program, the following indices weredecreased: BMI (p<0.001), glycemic level (p<0.001), HbCA1 (p=0.02), lipid profile (cholesterol, triglyceridesand LDL-C, p<0.001 for all). HDL-C was increased (p=0.01) In addition, physical activity was significantlyimproved: total activity and daily activity were increased ((p<0.001) and p=0.002, respectively).Conclusion: The ambulatory nurse education improves glycemic and lipidic control, BMI and physicalactivity in patients with cardiovascular disease.